Islam, secularism, and liberal democracy toward a democratic theory for Muslim societies - Hashemi, Nader 1966- (Oxford University Press, 2009)
Islam's relationship to liberal-democratic politics has emerged as one of the most pressing and contentious issues in international affairs. In Islam, Secularism, and Liberal Democracy, Nader Hashemi challenges the widely held belief among social scientists that religious politics and liberal-democratic development are structurally incompatible. This book argues for a rethinking of democratic theory so that it incorporates the variable of religion in the development of liberal democracy. In the process, it proves that an indigenous theory of Muslim secularism is not only possible, but is a necessary requirement for the advancement of liberal democracy in Muslim societies.